2018
DOI: 10.1111/idj.12381
|View full text |Cite
|
Sign up to set email alerts
|

Demographic profile, Oral Health Impact Profile and Dental Anxiety Scale in patients with chronic periodontitis: a case–control study

Abstract: Compared with controls, patients with chronic periodontitis had higher levels of dental anxiety and worse OHRQoL. It is important to consider dental anxiety and OHRQoL assessment as an integral component of the evaluation of patients with chronic periodontitis. Communication between dental and behavioral health professionals is needed to implement a multidisciplinary team approach involving behavioural and psychological interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 50 publications
5
43
1
2
Order By: Relevance
“…Levin et al. detected a lower OHIP‐14 score for patients with ChP especially in relationship to functional limitations, physical disability, psychological disability, and handicap . Other authors showed that psychological concerns, halitosis, pain, and esthetics mainly differ between periodontitis patients and others .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Levin et al. detected a lower OHIP‐14 score for patients with ChP especially in relationship to functional limitations, physical disability, psychological disability, and handicap . Other authors showed that psychological concerns, halitosis, pain, and esthetics mainly differ between periodontitis patients and others .…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies demonstrated periodontitis to negatively affect OHRQoL , . Sixty‐three patients with the baseline diagnosis generalized moderate (localized severe) or generalized severe chronic periodontitis were included in our study, limiting selection to diagnosis rather than to severity of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations